A model for the utilisation of networks and leveraging of the economic benefits of migration capital in emerging markets - Chunnett, Wanda Ingrid (Graduate School of Business (GSB), 2019)
The research considers the question: What can emerging market economies do to leverage sustainable growth opportunities from resource constrained, involuntary migrant entrepreneurs? It explores the positive economic impact that involuntary migrant entrepreneurs have made in an emerging market economy, South Africa, through the establishment of sustainable businesses. The objective is to understand the underlying enablers and constraints that facilitated the establishment of such businesses historically and to use them to develop a model that might be implemented by public and private institutions to maximise the economic benefits that groups of migrant entrepreneurs can deliver. It took the form of an inductive study of behavioural attributes to which a critical realist epistemology has been applied, using network theory and the lens of “desirable difficulties” within the context of social, economic and migration capital. The research was inspired by the work of Elizabeth and Robert Bjork (1996 and 2015) and extends the concept of desirable disabilities into the realm of societal “disabilities” that have been overcome by resource constrained migrant entrepreneurs, to accumulate the necessary social, knowledge and economic capital (Bourdieu, 1985) to establish sustainable businesses. The theoretical contribution of the research is to take the involuntary migrant debate beyond the "refugee as burden" paradigm, by focusing on constrained, involuntary migrants as potential economic contributors through: 1. A theoretical proposition that the legal, knowledge, language and economic capital required by constrained migrant entrepreneurs to leverage the enabling disabilities that they have and to establish their locus of power, is augmented by additional "migration capital", an offshoot of mobility capital, which originates from the interactions within and between the migrant group networks. 2. The development of a model, based on migration capital, which may be used by emerging market countries to maximise the economic growth opportunities that severely resource constrained entrepreneurs can offer. The model utilises a newly defined form of capital, namely migration capital, as its basis. It provides an alternative view to traditional, “push” based economic theories which have categorised refugees and migrants as economic burdens that must be supported by the host country for extended periods of time, to the detriment of the local population. The “pull” model is premised on the finding that migration is a temporal rather than geographic or ethnic issue and that there is additional value to be extracted over the lifespan of a migrant business if the social integration can be expedited through the facilitation of migration capital in addition to individual social, knowledge and economic capital. It considers the benefit that can be realised by the host country, where the process driver remains the migrant entrepreneur, eager to become established in a new country and achieve their long term vision.